Evaluation of the adequacy of good manufacturing procedures in foodservice establishments (Research, Society and Development, 2020)
The production of food using good manufacturing procedures is essential in food services. The objective of this study was to evaluate the conditions of food producing establishments regarding good manufacturing practices, including restaurants, snack bars, bakeries, butchers and pizzerias in the city of Dourados-MS. The assessment was made through the application of an instrument of federal legislation for food services. After analyzing the results, the establishments were classified according to the attendance of the items, in Group 1, the establishments that served from 76 to 100% of the items; Group 2, from 51 to 75% and Group 3, from 0 to 50%. It was also analyzed the attendance of the items buildings and facilities; equipment and utensils; manipulators; production and transportation of food and documentation, separately. Most of the establishments were classified as Group 2 (n = 32, 61.5%), and did not have a qualified technician in the area. Documentation and manipulators obtained the lowest adequacy indexes, 13.6 and 57%, respectively, in all evaluated establishments, with 71.2% of establishments reaching 100% inadequacy in the documentation aspect. Therefore, most establishments do not comply with current legislation regarding good food manufacturing practices.